Effectiveness of the Combination of Moving Bed Biofilm Reactor, Adsorption and Fenton Oxidation to Reduce Batik Waste Water Pollution - Ningrum, Dwi Mulyati; Hendrasarie, Novirina (Department of Environmental Engineering - Universitas Pasundan - Indonesia, 2025)
Batik wastewater has a high organic and color content, requiring special treatment to meet environmental quality standards. This wastewater has an initial BOD5 of 605.405 mg/L, COD 714 mg/L, TSS 360 mg/L, and Pt-Co color of 992.2, far exceeding the quality standards. This study aimed to determine the effectiveness of a Moving Bed Biofilm Reactor (MBBR) combination with rice husk geopolymer-based adsorption and Fenton oxidation post-treatment in removing pollutants from Sidoarjo batik wastewater. Variations in HRT, adsorbent mass, MBBR media type, and chemical ratio were the independent variables in this study. The results showed that the MBBR-adsorption treatment unit performed better than the MBBR without adsorption. The MBBR-adsorption unit with wood charcoal media, HRT 48 hours, and adsorbent mass 20 grams were the most optimal conditions for reducing COD and BOD5, with removal values of 93.6% and 95.8%, respectively. Meanwhile, the most optimal color and TSS removal was achieved with a 48-hour HRT MBBR adsorption, Kaldness K3 media, and 20 grams of adsorbent mass, with values of 90.3% and 94.4%, respectively. The addition of the Fenton process after the MBBR adsorption process increased the efficiency of TSS and color removal, with a FeSO₂:H₂O₂ ratio of 1:3, resulting in a 50% increase in TSS and 52.2% increase in color removal.